Persymmetric parametric adaptive matched filters for detecting targets using space-time adaptive processing of radar signals - SAHINOGLU ZAFER; PUN MAN-ON; WANG PU (2012)
A method provides space-time adaptive processing (STAP) for target detection using adaptive matched filters (AMF). A generalized likelihood ratio test (GLRT) is determined where spatial and temporal correlation matrices Q and A are assumed. Then, the correlation matrices A and Q are replaced with maximum likelihood (ML) estimates obtained only from training signals subject to a persymmetric constraint.